PENGARUH PELAYANAN ISLAMI DAN PROMOSI TERHADAP KEPUASAN PELANGGAN PADA OUTLET RABBANI KAMBANG KOTA JAMBI - Novera, Fika (Gapenas Publisher, 2025)
Although customer satisfaction in Muslim fashion retailers has been widely studied, research specifically comparing the influence of Islamic service and promotions on customer satisfaction at the Rabbani outlet in Kambang, Jambi City, is still limited. This study aims to analyze the influence of Islamic service and promotions on customer satisfaction, both partially and simultaneously. This study used a quantitative approach with a survey design, involving 100 Rabbani Kambang customer respondents selected through purposive sampling. Data were collected using a questionnaire and analyzed using the Partial Least Squares (PLS) method. The results show that Islamic service significantly influences customer satisfaction, while promotions have no significant effect. However, simultaneously, Islamic service and promotions have a positive effect on customer satisfaction. These findings contribute to the development of Islamic marketing theory, particularly regarding the role of Islamic service quality in shaping customer satisfaction. The study's conclusions emphasize the importance of consistently applying Islamic values ??in service as a key factor in increasing customer satisfaction and loyalty, and encourage management to develop creative promotional strategies that align with Sharia principles. The implications of this research include strengthening the Islamic marketing literature and providing practical recommendations for Muslim fashion retailers to improve service quality and promotional effectiveness based on Islamic values